Stability of food security in EU member states – does the common agricultural policy ensure resilience of food systems during crises? - Agnieszka Poczta-Wajda; Walenty Poczta (Ekonomista)
The COVID-19 pandemic and the Russian Invasion of Ukraine caused a global recession, not only by disrupting supply chains, raising inflation, and increasing public indebtedness, but also by destabilising global food markets. The resulting food shortages, along with the negative impact on the economic availability of food products, have made global inequalities more pronounced and exacerbated the problem of food insecurity. This study assesses the level and the stability of food security in the European Union (EU), compared to the rest of the world, and attempts to determine whether the common agricultural policy (CAP) has achieved its stated aim of creating resilient food systems. The stability of the first three dimensions of food security in various countries around the world was assessed based on the Global Food Security Index (GFSI). Research shows that food security in the EU is very good by world standards, as evidenced by the fact that 12 of the top 20 GFSI countries are EU member states. The CAP is shown to improve food security in EU member states and stabilises its already high level.